Prognostic role and clinical significance of C-reactive protein-lymphocyte ratio in colorectal cancer. Issue 1 (1st January 2021) - Meng, Yongsheng; Long, Chenyan; Huang, Xiaoliang; Huang, Lihaoyun; Liao, Lixian; Tang, Weizhong; Liu, Jungang
ABSTRACT: Systemic inflammatory response (SIRS) can be used as a potential prognostic marker in patients with colorectal cancer (CRC). The purpose of this study was to examine the predictive role of the C-reactive protein (CRP)-lymphocyte ratio (CLR) in the prognosis of CRC. We retrospectively analyzed the data of CRC patients who underwent surgery from 2004 to 2019. The clinicopathological characteristics and follow-up records were analyzed. According to a cutoff value of CLR, the patients were divided into the high and low groups. Kaplan–Meier curves and Cox proportional hazards regression model were applied to assess the overall survival (OS). Clinicopathological characteristics analysis showed that gender, age, BMI, lymphocyte count, tumor location, left- and right-sided CRC, differentiation, T stage, M stage, TNM stage, carcinoembryonic antigen (CEA), CLR, CRP, and microsatellite status were found to differ significantly between the high and low CLR groups. Kaplan–Meier curves revealed that the high CLR group had a shorter OS, and the elderly or right-sided CRC patients faced a worse prognosis. Multivariate analysis suggested that age (hazard ratio [HR]:1.011, P = 0.003), differentiation (HR:1.331, P = 0.000), TNM stage (HR:2.425, P = 0.000), CEA (HR:1.001, P = 0.025), CLR (HR:1.261, P = 0.014) were significant independent prognostic factors for OS. Subgroup analysis demonstrated that females or patients not receiving postoperative adjuvant chemotherapy with high CLR might suffer a worse prognosis. Overall, CLR can be applied as a promising prognostic marker in CRC patients and has great potential in guiding clinical work. Graphical abstract: uf0001